Exploring the inhibitors and triggers of social media users’ motivation for food photo sharing - Haoran Chen; Tianqi Chen; Chieh Yun Yang; Chen Kuo Pai; Yiming Gao (Cogent Social Sciences, 2024)
AbstractIn the current Internet era, Internet users can obtain and share information in various ways. Sharing photos with friends and other Internet users is one of the popular ways. Particularly, food photos occupy a large portion, and the activity of food content significantly influences social media and the restaurant industry. This study explains why people participate in online food photo-sharing communities by constructing an integrative model of online behavioral motivation. The study focuses on users of social media users in Beijing who use the platform to share food photos. A total of 320 questionnaires were distributed, of which 309 were collected as valid. Results show that personal and social intimacy concerns hinder users’ willingness to share food photos, whereas enjoyment, commitment and reputation-building positively trigger food photo sharing to a certain extent. The results provide practical suggestions for social media operators and relevant practitioners in the restaurant industry and references for them to adjust their strategies and launch relevant products in today’s fierce market competition.